A comparison between the simple kriging and the ordinary kriging methods for predicting the spatial distribution of the percentage of pollution SO4 in wastewater in Iraq (Entrepreneurship Journal for Finance and Business, 2021)
This search deals with the use of geographical statistics in estimate proportions of unmeasured pollution with chemical inorganic SO4  in governorates of Iraq except Kurdistan regional,   by using some  univariates  kriging models in spatial prediction by using simple kriging model and ordinary kriging model depending on the measured true data with their coordinates by using ARC10.4.1 and estimate the function value in one point from the close points . by using some semivariogram models (stable, spherical, exponential and Gaussian).and by using the more fitting from them. And by predictive mapping for pollution indications. the comparison was made by five criteria for spatial error indications those are (mean error, root mean square error , mean standardized error ,root mean square standardized error ,average standard error)the study found that ordinary kriging model by using semivariogram function of stable type was the best model for pollution data SO4.the SO4 pollution has been estimated in the un measured points(Ninawa , Salah Al-diyn Al-djyl ,Diyala , Karbala Al-Manfhan , Karbala Muharram eayshih ,Basra Al-Faw) the study showed  that SO4 pollution increase whenever we go towards south of Iraq